2013
DOI: 10.1093/mnras/stt1686
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous VLBA polarimetric observations of the v =   J = 1-0 and v =1, J = 2-1 SiO maser emission towards VY CMa: maser morphology and pumping

Abstract: This paper presents a component-level comparison of the polarized v=1 J =1-0, v=2 J=1-0 and v=1 J=2-1 SiO maser emission towards the supergiant star VY CMa at milliarcsecond-scale, as observed using the VLBA at λ = 7mm and λ = 3mm. An earlier paper considered overall maser morphology and constraints on SiO maser excitation and pumping derived from these data. The goal of the current paper is to use the measured polarization properties of individual co-spatial components detected across multiple transitions to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 137 publications
(295 reference statements)
0
8
0
Order By: Relevance
“…It is therefore expected that the emitting volumes change from one maser to another. This is confirmed by interferometry at low v-states (e. g. Gonidakis et al 2010;Kamiński et al 2013;Richter et al 2013). Such restrictive physical conditions are met through different mechanisms (radiative pumping, collisional pumping, overlaps), as explained in Sect.…”
Section: About the Emitting Regionmentioning
confidence: 61%
“…It is therefore expected that the emitting volumes change from one maser to another. This is confirmed by interferometry at low v-states (e. g. Gonidakis et al 2010;Kamiński et al 2013;Richter et al 2013). Such restrictive physical conditions are met through different mechanisms (radiative pumping, collisional pumping, overlaps), as explained in Sect.…”
Section: About the Emitting Regionmentioning
confidence: 61%
“…Exponential maser amplification exaggerates small differences in conditions, so single-epoch data are interpreted with caution. The 658 GHz masers have a complex distribution close to the star, but mostly outside the typical SiO outer rim, taken from Richter et al (2013), as shown in Fig. 6 (although found a more extended bipolar outflow).…”
Section: Discussionmentioning
confidence: 80%
“…The 658 GHz masers have a complex distribution close to the star, but mostly outside the typical SiO outer rim, taken from Richter et al (2013), as shown in Fig. 6 (although Shinnaga et al (2004) found a more extended bipolar outflow).…”
Section: Discussionmentioning
confidence: 86%
“…Consequently, our results strongly imply that the spokelike features of the v=1 and v=2 J=1→0 SiO masers are kinematically coupled. Nevertheless, with only this result, we cannot argue which pumping mechanism is dominant in the v=1 and v=2 J=1→0 SiO masers because boththe radiative and the collisional pumping models predict the strong physical links between these SiO masers (Humphreys et al 2002;Soria-Ruiz et al 2004;Gray et al 2009;Richter et al 2013;Desmurs et al 2014). …”
Section: Discussionmentioning
confidence: 87%